Upper airway gene expression reveals suppressed immune responses to SARS-CoV-2 compared with other respiratory viruses - Mick, Eran; Kamm, Jack; Pisco, Angela Oliveira; Ratnasiri, Kalani; Babik, Jennifer M.; Castañeda, Gloria; DeRisi, Joseph L.; Detweiler, Angela M.; Hao, Samantha L.; Kangelaris, Kirsten N.; Kumar, G. Renuka; Li, Lucy M.; et al. (Nature communications, 2020)
SARS-CoV-2 infection is characterized by peak viral load in the upper airway prior to or at the time of symptom onset, an unusual feature that has enabled widespread transmission of the virus and precipitated a global pandemic. How SARS-CoV-2 is able to achieve high titer in the absence of symptoms remains unclear. Here, we examine the upper airway host transcriptional response in patients with COVID-19 ( n = 93), other viral ( n = 41) or non-viral ( n = 100) acute respiratory illnesses (ARIs). Compared with other viral ARIs, COVID-19 is characterized by a pronounced interferon response but attenuated activation of other innate immune pathways, including toll-like receptor, interleukin and chemokine signaling. The IL-1 and NLRP3 inflammasome pathways are markedly less responsive to SARS-CoV-2, commensurate with a signature of diminished neutrophil and macrophage recruitment. This pattern resembles previously described distinctions between symptomatic and asymptomatic viral infections and may partly explain the propensity for pre-symptomatic transmission in COVID-19. We further use machine learning to build 27-, 10- and 3-gene classifiers that differentiate COVID-19 from other ARIs with AUROCs of 0.981, 0.954 and 0.885, respectively. Classifier performance is stable across a wide range of viral load, suggesting utility in mitigating false positive or false negative results of direct SARS-CoV-2 tests. Here, the authors provide upper airway gene expression data from patients with COVID-19 and other viral and non-viral acute respiratory illnesses. They find attenuated activation of innate immune and pro-inflammatory pathways in COVID-19 as compared to other viral infections, which may contribute to its propensity for pre-symptomatic transmission.